DYNAMICS OF NUTRITION ELEMENTS IN FODDER CROPS AGROCENOUSES - Vlasenko, O A (Mongolian Journal of Agricultural Sciences, 2018)
Rapeseed and rapeseed and millet mixtures are cultivated, the supply of chernozem with nitrate nitrogen is low and medium, the supply of ammonium nitrogen is high. The availability of mobile phosphorus is reduced by the end of the growing season. The availability of exchange potassium for these crops is very high.